Rare Earth Complexes of Some Substituted Chalcones - Akuskar, S.K.; Shankarwar, A.G.; Dhuley, D.G.; Chondhekar, T.K. (Asian Journal of Chemistry, 2010)
The present paper reports (a) the synthtesis of a series of chalcones from ortho-hydroxy acetophenones with p-nitromethy/benzoic acid and benzaldehyde/anisaldehyde, (b) the determination of their pK values and the study of their complexation with some metal ions in lanthanide series.